The long-period Galactic Cepheid RS Puppis: III. A geometric distance from HST polarimetric imaging of its light echoes - Kervella, P.; Bond, H. E.; Cracraft, M.; Szabados, L.; Breitfelder, J.; Mérand, A.; Sparks, W. B.; Gallenne, A.; Bersier, D.; Fouqué, P.; Anderson, R. I. (Astronomy and astrophysics (Berlin), 2014)
As one of the most luminous Cepheids in the Milky Way, the 41.5-day RS Puppis is an analog of the long-period Cepheids used to measure extragalactic distances. An accurate distance to this star would therefore help anchor the zero-point of the bright end of the period-luminosity relation. But, at a distance of about 2 kpc, RS Pup is too far away for measuring a direct trigonometric parallax with a precision of a few percentage points with existing instrumentation. We present new polarimetric imaging of the nebula obtained with HST/ACS. The RS Pup therefore provides an important fiducial for calibrating the systematic uncertainties of the long-period Cepheid distance scale.